Hindmilk for procedural pain in term neonates - (:unkn) unknown (TURKISH J PEDIATRICS, 2010)
Altun-Koroglu O, Ozek E, Bilgen H, Cebeci D. Hindmilk for procedural pain in term neonates. Turk J Pediatr 2010; 52: 623-629. The aim of this study was to investigate whether repeated doses of hindmilk were effective for pain relief during routine heel stick in term neonates. Infants enrolled in this double-blind placebo-controlled study were randomly assigned to hindmilk, 12.5% sucrose and distilled water groups. Infants were given 1 ml of the test solution 1 minute prior to, immediately before and 1 minute after the heel stick. Pain responses were assessed by physiologic and behavioral parameters and also according to the Neonatal Facial Coding System (NFCS). There were significant reductions in crying time, duration of the first cry and tachycardia, time needed for return to baseline heart rate, and the average and 1- and 5-minute NFCS scores in the hindmilk group when compared with the distilled water group. When the hindmilk group was compared to the sucrose group, only the NFCS scores at 1 and 2 minutes reached statistical significance in favor of the sucrose group. Repeated dose hindmilk administration is an effective analgesic intervention in term newborns during heel stick. Although the analgesic effect of 12.5% sucrose is slightly superior, hindmilk may be considered as a physiologically suitable alternative to sucrose.
Keywords: analgesia; heel stick; hindmilk; newborn; pain; breast milk; MILK; ANALGESIA; SUCROSE; INFANTS; RATS